The Formulation and Test of Antioxidant Activity from Serum Gel of the Extract Chrysanthemum Flower (Chrysanthemum Indicum L.) - Shelly Taurhesia; Dellia Nursyifa Rosdiana; Diah Kartika Pratami (Journal of Natural Product for Degenerative Diseases, 2024)
Skin as the outermost layer of the body will be first exposed to UV light, and pollution which may form free radicals and lead to premature aging, so the application of antioxidants is indispensable. One of the skin cares that are in great demand is serum. A plant that has a high content of antioxidants and is widely cultivated in Indonesia is the chrysanthemum flower (Chrysanthemum indicum L.). Previous research stated that the IC50 value of chrysanthemums was 43.34 ppm. This study aimed to determine the IC50 value contained in chrysanthemum flower extract and formulate it into serum gel that contains antioxidants and meets physical parameters. The method used in determining the IC50 value is the DPPH method. The formulation was carried out by adding different levels of chrysanthemum flower extract to the formula. The evaluation test includes organoleptic, pH, spreadability, viscosity, and antioxidant activity and stability test at room temperature (25oC) and high temperature (40oC). The results obtained were IC50 values of chrysanthemum flower extracts was 32.78 ± 0.01 ppm while the IC50 of serum gel were 109.10 ± 0.1 ppm (F1) and 73.51 ± 0.08 ppm (F2) and after 4 weeks stored at room temperature the IC50 114.02 ± 0.09 ppm (F1) and 76.39 ± 0.06 ppm (F2). The conclusion is that chrysanthemum flower extract has a very strong antioxidant activity, and the serum gel has a strong antioxidant activity and is stable at both room temperature and 40oC for 4 weeks.